Epidemiological statistics of adolescent suicide during confinement due to the Covid-19 pandemic in Ecuador: Estadística epidemiológica del suicidio adolescente durante confinamiento por pandemia de Covid-19 en Ecuador - Chávez, Andres Joaquin Guarnizo (2021)
Introduction: Adolescent suicide is a public health problem that has been neglected due to the pandemic and confinement. Objective: To describe the characteristics of adolescent suicide, during the period of confinement due to pandemic in the year 2020 in Ecuador. Method: An observational, descriptive, cross-sectional, retrospective study was carried out, with the information from the database of violent deaths of the Ministry of Government, from March 17 to September 13, which lasted through the state of emergency. The analysis was carried out by province, sex, age, suicide method and frequency in days after the event occurred. The suicide mortality rate (per 100,000 inhabitants) was estimated for each province. Results: During confinement due to a state of emergency in 2020 in Ecuador, 97 suicides were registered among adolescents between 10 and 19 years of age. The highest number was estimated in males between 15 and 19 years of age, with the most frequent age being 19. The most frequent day of removal of corpses was on Mondays, and the preferred mode of suicide was by hanging with 81 reported cases. followed by intoxication and poisoning. Conclusions: No increases were found in the suicide mortality rate during the state of emergency in 2020. However, it must be considered that the context of COVID-19 has increased the burden of psychological suffering, which may lead adolescents to think about suicide.